Characteristics of tropical cyclones making landfall on the Pacific coast of Mexico: 1970-2010 - Farfán Molina, Luis Manuel (2013)
Artículo científico -- Universidad de Costa Rica, Centro de Investigaciones Geofísicas. 2013